Multi-Layered Security System Using Cryptography and Steganography (International Journal of Innovative Research in Computer Science & Technology, 2019)
The Internet as a whole does not use secure  links, thus information being transmitted may be  vulnerable to interception as well. The importance of  reducing the chances of information being detected  during transmission is a major issue. A solution to be  discussed is how passing of information can be done in a  manner that the very existence of the message is  unknown. This is important in order to repel attention  from the potential attacker. Besides hiding data for  confidentiality, this approach of information hiding can  be extended to copyright protection of digital media. In  this work, we focus on the achievement of a  multi-layered security system by combining both  cryptography and steganography. Encryption avoids  passive attacks (reading) and by steganography, the  message becomes undetectable. We make use of AES  algorithm and Least Significant Bit (LSB) technique for  hiding messages in an image. We have enhanced the  LSB technique by randomly dispersing the bits of the  message in the image and thus making it harder for an  unauthorized person to extract the original message.  The AES provides a good security as it takes  considerably much more time to break by the brute  force method for a given key length. The proposed  methodology is proved good and produced expected  output.
Keywords: Information Security; Cryptography; Steganography